2018
DOI: 10.3390/genes9020070
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Identification and Expression Analysis of the HD-Zip Gene Family in Wheat (Triticum aestivum L.)

Abstract: The homeodomain-leucine zipper (HD-Zip) gene family, as plant-specific transcription factors, plays an important role in plant development and growth as well as in the response to diverse stresses. Although HD-Zip genes have been extensively studied in many plants, they had not yet been studied in wheat, especially those involved in response to abiotic stresses. In this study, 46 wheat HD-Zip genes were identified using a genome-wide search method. Phylogenetic analysis classified these genes into four groups,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
44
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(47 citation statements)
references
References 67 publications
1
44
0
2
Order By: Relevance
“…Contribution of homoeolog expression dominance in facilitating selection of glucosinolate and lipid metabolism genes was also reported in the vegetable-use and oil-use sub-varieties of Brassica juncea 51 . In cotton and wheat, alterations of expression patterns among homoeologs under variation in stress conditions, tissues, and developmental stages have also been documented [52][53][54][55][56][57] . Given the consequences of unequal expression to the natural gene selections in polyploids, it is important to understand the genetic basis of valuable traits with respect to the homology and homoeology perspectives for the success of selective breeding programs.…”
mentioning
confidence: 97%
“…Contribution of homoeolog expression dominance in facilitating selection of glucosinolate and lipid metabolism genes was also reported in the vegetable-use and oil-use sub-varieties of Brassica juncea 51 . In cotton and wheat, alterations of expression patterns among homoeologs under variation in stress conditions, tissues, and developmental stages have also been documented [52][53][54][55][56][57] . Given the consequences of unequal expression to the natural gene selections in polyploids, it is important to understand the genetic basis of valuable traits with respect to the homology and homoeology perspectives for the success of selective breeding programs.…”
mentioning
confidence: 97%
“…NORMAL=1). In a recently study, a total of 46 HD-Zip genes were identified in wheat by a genomewide bioinformatic survey [35]. In this study, we further identified 67 additional HD-Zip genes in wheat latest genome and extended the total member to 113.…”
Section: Identification Of the Hd-zip Gene Family In Wheatmentioning
confidence: 87%
“…We kept predicted proteins with both identity and coverage higher than 0.5. According to previous homologous gene identification methods 25, 26 , we also we performed pairwise alignments for all protein sequence, using CD-HIT 27 with the parameters of identity > 90% and coverage > 70%. In this way Coronavirus proteins are clustered into 322 unified gene clusters.…”
Section: Methodsmentioning
confidence: 99%